A meta-analysis exploring the relationship between psychopathy and instrumental versus reactive violence - Blais, Julie (Criminal justice and behavior, 2014)
The present meta-analysis explored the relationship between psychopathy and instrumental and reactive violence with a focus on factor and facet scores. A total of 53 studies (reporting on 55 unique samples, N = 8,753) from both published and unpublished sources were included. Results from random-effects analyses indicated moderate and significant relationships between psychopathy and both instrumental and reactive violence. There was some evidence that the Interpersonal facet was more important for instrumental violence, while Factor 2 (social deviance) was more important for reactive violence. The Lifestyle facet appeared important in explaining both violent outcomes. Effect sizes were significantly smaller for clinical rating scales compared with informant and self-report scales. Significant between-study variability was partly explained by mean age of the sample and type of outcome measure. The current findings do not support the conclusion that psychopathy is more related to instrumental violence as opposed to reactive violence.